Study on Changes of Thermophysical Properties and Mechanical Parameters of Rat Skin during Heating Process - Zhang Xilong; Zhu Kai; Wang Yabo; Song Ting (Zhileng xuebao)
Current research on the properties of skin is far from perfect. This poses certain difficulties for hyperthermia and related clinical research. Rats were used as experimental subjects to study the changes of thermophysical properties and mechanical parameters during heating and the influence of temperature and moisture was discussed. The results suggested that the stress and strain curves of the skin tissue were approximately linear during heating (37–47 ℃). The elastic modulus was related to the temperature and decreased gradually when the temperature increased. As the temperature increased, Poisson's ratio for the tissue changed similarly. In addition, during the initial stage of heating (37-45 ℃), the water content of the tissue was not significantly reduced. The thermal conductivity increased very slowly with the increasing temperature and remained almost unchanged. However, as the temperature and time increased, the tissue began to lose water. The effect of the water content on the thermal conductivity was higher than the effect of the temperature. When the temperature reached 45 ℃, the thermal conductivity began to drop sharply;from 45 ℃ to 47 ℃, the thermal conductivity value decreased by 5.4% and the specific heat capacity changed similarly.